2016
DOI: 10.1089/ars.2015.6539
|View full text |Cite
|
Sign up to set email alerts
|

TCF11/Nrf1-Mediated Induction of Proteasome Expression Prevents Cytotoxicity by Rotenone

Abstract: Using the human dopaminergic neuroblastoma cell line SH-SY5Y and mouse nigrostriatal organotypic slice cultures, gene and protein expression analysis and functional assays revealed oxidative stress is induced by the proteasome inhibitor epoxomicin or the mitochondrial complex I inhibitor rotenone and promotes the upregulation of proteasome expression and function mediated by TCF11/Nrf1 activation. In addition, we show that these stress conditions induce the unfolded protein response. TCF11/Nrf1, thus, has a cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 73 publications
11
41
0
Order By: Relevance
“…Overall, it is important to note that a lower dose (1 µmol/L) of MG132 only gave rise to a dominant stimulation signal to activate the PERK-elF2 pathway (Figure 8, C4 to C7), with a weak signal of XBP-1s but not of ATF6-N. By contrast, striking signals of XBP-1s and ATF6-N appeared to be activated by a higher dose ( oxidative) besides ER stress. Together with the above results (as shown in Figure 3) and a previous report by another group [70], these findings demonstrate that distinct extents of oxidative stress and antioxidant response signaling are significantly induced by different concentrations of MG132, particularly at a higher dose of the proteasomal inhibitor, resulting in marked increases in the expression of Nrf2-target antioxidant genes (Figure 9). In addition, it is intriguing to note that the aspartic protease DDI-1 per se also appeared to be processed under modest ER stress induced by 1 µmol/L of TG or MG132 ( Figures 8C10, 8D10, S8C).…”
Section: Distinct Processing Of Nrf1 Under Distinct Stresses Inducedsupporting
confidence: 89%
See 3 more Smart Citations
“…Overall, it is important to note that a lower dose (1 µmol/L) of MG132 only gave rise to a dominant stimulation signal to activate the PERK-elF2 pathway (Figure 8, C4 to C7), with a weak signal of XBP-1s but not of ATF6-N. By contrast, striking signals of XBP-1s and ATF6-N appeared to be activated by a higher dose ( oxidative) besides ER stress. Together with the above results (as shown in Figure 3) and a previous report by another group [70], these findings demonstrate that distinct extents of oxidative stress and antioxidant response signaling are significantly induced by different concentrations of MG132, particularly at a higher dose of the proteasomal inhibitor, resulting in marked increases in the expression of Nrf2-target antioxidant genes (Figure 9). In addition, it is intriguing to note that the aspartic protease DDI-1 per se also appeared to be processed under modest ER stress induced by 1 µmol/L of TG or MG132 ( Figures 8C10, 8D10, S8C).…”
Section: Distinct Processing Of Nrf1 Under Distinct Stresses Inducedsupporting
confidence: 89%
“…All together with the previous evidence provided by us and other groups from immunocytochemical staining of distinct Nrf1 isoforms, subcellular fractionation, and live-cell imaging combined with membrane protease protection assays [11,39,43,44,70], these demonstrated that protein- Nrf1/TCF11 and its aggregated proteins are also examined, particularly following treatment of cells with a higher concentration of proteasomal inhibitors [55,70,71].…”
Section: Establishment Of a Generally Acceptable Criterion To Identifmentioning
confidence: 58%
See 2 more Smart Citations
“…As shown in Figure 4, control cells exposed to carfilzomib could successfully compensate the applied proteotoxic stress by increasing their pools of intracellular proteasomes, as evidenced by elevated expression of all investigated β-and Rpt-subunits. As expected, this process was preceded by the processing of the ER membrane-resident protein TCF11/Nrf1 ( Figure 4A), which is the transcription factor acting on nuclear genes encoding 19S and 20S proteasome subunits (Steffen et al, 2010;Radhakrishnan et al, 2010;Sotzny et al, 2016). Strikingly, the level of processed TCF11/Nrf1 in response to carfilzomib was much lower in cells carrying the homozygous PSMC3 pathogenic variant than that observed in control cells.…”
Section: Functional Effect Of the Psmc3 Variant To The Proteasome Funsupporting
confidence: 66%